GAMBARAN PERILAKU CARING PERAWAT DI RUANG ANGGREK BADAN RUMAH SAKIT UMUM DAERAH KABUPATEN TABANAN - Apriani, Desak Gede Yenny; Putri, Desak Made Firsia Sastra; Widiyani, Ni Putu Dewi (LPPM STIKES MUHAMMADIYAH GOMBONG, 2020)
DESCRIPTION CARING BEHAVIOR OF NURSE AT PEDIATRIC CARE UNIT IN TABANAN GENERAL HOSPITAL Desak Gede Yenny Apriani1,2, Desak Made Firsia Sastra Putri1,2, Dewi Widiyani1,21S1 Keperawatan Ners, 2STIKES Advaita Medika Tabanan,Correspondence: yennyapriani2004@gmail.com ABSTRACT Introduction: nurse is a person who have a skill and allowance to do medical treatment based on prior knoledge and collected from education in term of nursing. Caring is a maintainingrelationships with mutual respect for other accompanied by feeling of belonging and responsibility. Caring behavior is an emotional support in providing nursing care to protect patient, enhance human dignity, and it was the care wich made a diffrence from other profession. Turpose to know description caring behavior of nurse at Pediatric Care Unit Method: this study was a descriptive analytic with cross sectional approach. The responden was chosen based on total sampling which were 13 samples by using observation sheet. Result: This study showed that caring behaviot of nurse at Pediatric Care Unit 13 nurse (100%) was in good category, with sub variable according to five dimension of Swanson theory that is maintaining belief with mean 57,7%. Sub variable knowing of nurse (100%) was in good category with mean 92,3%, sub variable being with was good category 13 nurse (100%) with mean 96,5%. Doing for behavior so as in good category 16 nurse (100%) with mean 98,5% and enabling behavior in good category 16 nurse (100%) with mean 80%. Discussion: caring behavior of nurse at Pediatric Care Unit at Tabanan General Hospital is good category. Keywords: Caring Behavior, Nurse, Pediatric Care Unit